Pengamanan Data Menggunakan Citra Medis Berbasis Steganografi dengan Discrete Cosine Transform dan Least Significant Bit - Hanif Faishal (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
In the medical sector, patient data contains highly sensitive information and must be adequately protected from unauthorized access. Medical images are a crucial form of digital imagery in healthcare, as they contain all the patient's information. If patient information is not secured, it can be used for crimes or data misuse. So, the solution for securing medical images is steganography with discrete cosine transformation and the least significant bit methods. With the results of the stego image that is visible to the naked eye. Also, the test results using MSE and PSNR show that the better the image quality, the better the quality of the stego image.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Security Data; Medical Imaging; Steganography; Discrete Cosine Transform; Least Significant Bit